2014
DOI: 10.1002/2014ja019847
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric variability over Indian low latitude linked with the 2009 sudden stratospheric warming

Abstract: In this paper, we analyze radar observations of E × B drift and plasma irregularities, ionosonde observations of E and F layer parameters including spread F, and magnetic field observations made from Indian low latitudes linked with the 2009 sudden stratospheric warming (SSW) event. E × B drift variations presented here are the first of their kind from the Indian sector as far as the effect of SSW is concerned. Difference of magnetic fields observed from the equator and low-latitude (ΔH) and E × B drift show l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
0
24
1
Order By: Relevance
“…They restricted the analysis to the days around SSW period (i.e., January 2009), and the variability thereafter had not been explored. Similarly, Patra et al () investigated the variation of EEJ during the 2009 SSW event over the Indian region, but their study also could not highlight the occurrence of two intense CEJ events reported in the present study. The strong semidiurnal perturbation observed in the zonal wind, EEJ, and TEC around new and full moon phases unambiguously suggests the amplification of semidiurnal lunar tide during the 2009 SSW event.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…They restricted the analysis to the days around SSW period (i.e., January 2009), and the variability thereafter had not been explored. Similarly, Patra et al () investigated the variation of EEJ during the 2009 SSW event over the Indian region, but their study also could not highlight the occurrence of two intense CEJ events reported in the present study. The strong semidiurnal perturbation observed in the zonal wind, EEJ, and TEC around new and full moon phases unambiguously suggests the amplification of semidiurnal lunar tide during the 2009 SSW event.…”
Section: Discussioncontrasting
confidence: 72%
“…The absence of quasi 16 day periodicity around the NE stations suggests that the ionization over NE stations do not get influenced by the EEJ and the consequent fountain effect. The earlier workers also reported the presence of quasi 16 day wave during the SSW events at the low‐latitude ionosphere of the Indian zone, which are linked with the changes in the equatorial electric fields (Laskar et al, ; Patra et al, ; Sripathi & Bhattacharyya, ). The presence of quasi 16 day wave during the SSW event of 2013 was also observed over midlatitude ionosphere (Chen et al, ).…”
Section: Discussionmentioning
confidence: 93%
“…[] have compared the vertical drifts obtained by using 150 km echoes at Gadanki and C/NOFS ion drift measurements and suggested that 150 km echoes do represent vertical drifts during daytime. In fact they also compared their drifts with EEJ strength on monthly basis and found that they are in good agreement [ Patra et al ., ]. While their drifts are comparable to C/NOFS ion drifts in magnitude, however, SF drift model could not reproduce these drifts when drifts are either lower or higher.…”
Section: Discussionmentioning
confidence: 90%
“…Considering that large vertical E × B drift can significantly reduce the F2 layer density and form an additional layer (the F3 layer), we would expect an inverse relationship between vertical E × B drift and f oF2. In order to gain some insight into this phenomenon, we have used H data as proxy of E × B drift (Anderson et al, 2002;Patra et al, 2014) and examined the relationship between H and f oF2. Figure 7 shows scatter plots displaying the relationship between the two in different solar activity conditions.…”
Section: Equinoxial and Solstice Asymmetriesmentioning
confidence: 99%